Voices represented and voices silenced: Represented voices in the media coverage of the implementation of a supervised injecting facility - Whiteside, Bianca; Dunn, Matthew (The International journal of drug policy, 2023)
•Victoria's first medically supervised injecting room (MSIR) remains controversial.•The media play a fundamental role in shaping public opinion and political debate.•Representations of the MSIR were debated by three predominant actors.•Experiences of people who inject drugs are largely silenced in the sample. Victoria's first medically supervised injecting room (MSIR) has remained controversial despite mounting evidence in support of the facility. The opposition to a policy idea is subject to a myriad of factors including the media. Favouring the opinions of various actors, the media are a fundamental element of the narrative formation process. In this article, we examine the voices represented and voice silenced in print news media and the possible effects of such reporting. A quantitative content and qualitative thematic analysis of Victorian print media (n=645) focusing on the implementation and continued operation of North Richmond Community Health's medically supervised injecting room was conducted. The representations of the MSIR were debated by three predominant actors – politicians, public, and residents. Politicians largely relied on the ‘saving lives’ rhetoric when supporting the facility. In addition, competing representations of ‘public amenity’ were presented by both advocates and proponents of the MSIR. We found the voices of people who inject drugs were inadequately represented within the data. Instead, overdose statistics were featured as were discursive descriptions of people who inject drugs such as ‘addicts’, ‘junkies’, and ‘druggies’. Despite people who inject drugs being the population the MSIR is designed to benefit, their experiences and voices were lacking, highlighting social power structures, denying the silenced power, and obstructing social change. Overdose rates were consistently presented as numbers, negating personal experiences and lacking meaningful debate. Further, negative discourse referring to people who inject drugs may have implications regarding internalised and externalised stigma and drug policy.